2018
DOI: 10.34208/jba.v15i2.146
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF CORPORATE GOVERNANCE MECHANISM ON EARNINGS MANAGEMENT PRACTICE (Case Study on Indonesia Manufacturing Industry)

Abstract: The purpose of the research is to get empirical evidence about institutional ownership, management ownership, directors’ size, audit committee, independent commissioner, leverage, profitability, firm size, auditor’s independency and auditor’s reputability on earnings management practice. This research used 53 manufacturing companies listed in Indonesia Stock Exchange and the data were collected through purposive sampling method during the research period 2009 until 2011. The result of the research showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 21 publications
5
27
0
14
Order By: Relevance
“…Ngamchom shows that board independence has negative correlation with earnings management [3]. This study has the same result with Xie et al, Johari el al, and Susanto et al [12][13][14], the greater the number of independent directors in the company, the better monitoring over management, which will reduce earnings management practices. On the contrary, Abdullah using data from Kuala Lumpur Stock Exchange (KLSE) showed that there's no significant relationship between board independence and earnings management [11].…”
Section: H1 Board Size Has Influence On Earnings Management B Board supporting
confidence: 78%
See 3 more Smart Citations
“…Ngamchom shows that board independence has negative correlation with earnings management [3]. This study has the same result with Xie et al, Johari el al, and Susanto et al [12][13][14], the greater the number of independent directors in the company, the better monitoring over management, which will reduce earnings management practices. On the contrary, Abdullah using data from Kuala Lumpur Stock Exchange (KLSE) showed that there's no significant relationship between board independence and earnings management [11].…”
Section: H1 Board Size Has Influence On Earnings Management B Board supporting
confidence: 78%
“…The empirical evidence from Susanto research showed that woman in audit committees negatively correlated to earnings management [4]. This result is supported by Man and Qi [18,19], female audit committees tend to be risk-averse to fraud and engage in less earnings management.…”
Section: G Audit Committees Woman and Earnings Managementmentioning
confidence: 85%
See 2 more Smart Citations
“…Profitability is measured by the proxy of ROA measurement that is the ratio between net profit after tax which is obtained with total assets of company (Alzoubi 2016). (9) Leverage is the percentage of company assets financed by using debt (Susanto, 2013).…”
Section: (7)mentioning
confidence: 99%